KARAKTERISTIK PENDERITA KANKER PAYUDARA RAWAT INAP DI RS. HAJI MEDAN TAHUN 2014-2015 - fitri lingga; Rasmaliah .; Sri Novita Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Abstract Breast cancer ranks first globally of all cancers in women with a prevalence rate of 56.5 per 100,000 women. Indonesia is ranked 2nd after cervical cancer. Meanwhile, from the Ministry of Health of Indonesia North Sumatra in the category of top 10 highest of the 33 provinces in Indonesia. Research is a descriptive with case series design at the Hospital Haji Medan start from January to June 2016. The population totaled to 447 people and the sample totaled to 96 people. Data obstained medical records, data analyzed by Chi-square test. This research aims to know the characteristics of breast cancer patients hospitalized in Hospital Haji Medan Year 2014-2015. The results show the highest proportion of breast cancer patients at the ages ≥40 years (74,0%), Java (54.2%), Islam (94.8%), SLTA (38.5%), IRT ( 79.3%), married (82.3%), Deli Serdang (72.9%), with complaints seen (68,8%), upper lateral quadrant layout cancer (39.5%), examination PA (88.5%), advanced (67.7 %) with stage IIIB (30.2%), surgery (31.3%), Askes/BPJS (83.4%), the average length of treatment <7 days (53.1%), return outpatient (65.6%). Statistical test results found no differences between age based on clinical stage (p = 0.051), education based on clinical stage (p=0.113%), examination of the PA based on clinical stage (p = 0.321), medical management based examination of the PA (p=0,999), medical management based clinical stage (p= 0.712%), duration of treatment average based on clinical stage (p = 0.838%), clinical stage based on the state when the home (p = 0.281%). For the Hospital Haji Medan is expected to complete supporting facilities for the treatment with radiotherapy and to complete of the medical record regarding family history. The public are advised to perform breast self-examination and checking her self to the hospital a health service or a doctor it find a lump in breast/axilla area . Key words : Breast cancer, Patient Characteristics, Breast Self- examination.